2012
DOI: 10.1634/theoncologist.2011-0458
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Somatostatin Analogs in Neuroendocrine Tumors

Abstract: Background. For decades, somatostatin analogs (including octreotide and lanreotide) have been indicated for relief of the symptoms of flushing, diarrhea, and wheezing associated with secretory neuroendocrine tumors (NETs). Recently, it has been suggested that somatostatin analogs may provide direct and indirect antitumor effects in secretory and nonsecretory NETs in addition to symptom control in secretory NETs.Methods. A systematic review of MEDLINE was conducted to identify studies that investigated the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 49 publications
2
69
0
3
Order By: Relevance
“…Eriksson and Oberg found that, in studies of octreotide spanning its introduction up to the late 1990s, approximately half of the patients with GEP-NET achieved stabilization of tumour growth (i.e., no increase or decrease in tumour size), with 10-20% showing tumour regression (Eriksson & Oberg 1999). A more recent review that analysed trials conducted between 1987 and 2011 revealed that stable disease in patients with poorly differentiated, functioning or non-functioning GEP-NET was achieved in up to 86% treated with octreotide sc and up to 88% in those receiving octreotide LAR (Sideris et al 2012). Partial tumour response (i.e., a predefined reduction in overall tumour load) reached 31 and 11% for octreotide sc and octreotide LAR, respectively, broadly in agreement with the earlier findings by Eriksson and Oberg (Eriksson & Oberg 1999).…”
Section: Antitumour Effectmentioning
confidence: 99%
“…Eriksson and Oberg found that, in studies of octreotide spanning its introduction up to the late 1990s, approximately half of the patients with GEP-NET achieved stabilization of tumour growth (i.e., no increase or decrease in tumour size), with 10-20% showing tumour regression (Eriksson & Oberg 1999). A more recent review that analysed trials conducted between 1987 and 2011 revealed that stable disease in patients with poorly differentiated, functioning or non-functioning GEP-NET was achieved in up to 86% treated with octreotide sc and up to 88% in those receiving octreotide LAR (Sideris et al 2012). Partial tumour response (i.e., a predefined reduction in overall tumour load) reached 31 and 11% for octreotide sc and octreotide LAR, respectively, broadly in agreement with the earlier findings by Eriksson and Oberg (Eriksson & Oberg 1999).…”
Section: Antitumour Effectmentioning
confidence: 99%
“…Octreotide and lanreotide are somatostatin analogs proved to be useful in alleviation of of flushing and diarrhea which are associated with NETs secretion (55,56). The antitumor effect of somatostatin analogs has been established in many clinical trials (57)(58)(59).…”
Section: Neuropeptides and Cancermentioning
confidence: 99%
“…Again, both these analogs have been reported to have an antiproliferative effect in vitro [52,53] . Data from uncontrolled prospective and retrospective clinical series [54][55][56] showed tumor shrinkage and disappearance in response to either short-acting SSAs alone or when combined with interferon-α. Further trials have reported tumor stabilization in up to 50% of patients, but without complete regression.…”
Section: Management Of Type-i Gastric Carcinoid -A Clinical Challengementioning
confidence: 99%